2019
DOI: 10.3390/met9101050
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Rusted Rebar and Enhanced Passivation/Anticorrosion Performance in Simulated Concrete Pore Solutions with Different Alkalinity

Abstract: Naturally exposed rusted rebar has been widely used for the production of reinforced concrete. However, rusted rebar is prone to corrosion under chloride ion (Cl−) contamination and/or at a low alkalinity of concrete. This study employed two surface modification methods, sand blasting and wire brushing, to augment the corrosion resistance of naturally exposed rusted rebar. Electrochemical tests revealed that the surface-modified rebar displayed a significant improvement of passivation in the concrete alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…These environmental loads are also the major factor that are controlling the corrosion rate of rebar. The moisture amount within the concrete governs the corrosion rate through their influence on the electrochemical reactions at the rebar-concrete interface and ions transport between anodes and cathodes [12]. The surrounding temperature controls the rate of rebar corrosion since it influences the electrochemical reactions and the moisture amount that the concrete retains [135].…”
Section: Evolution Of Data-driven Corrosion Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These environmental loads are also the major factor that are controlling the corrosion rate of rebar. The moisture amount within the concrete governs the corrosion rate through their influence on the electrochemical reactions at the rebar-concrete interface and ions transport between anodes and cathodes [12]. The surrounding temperature controls the rate of rebar corrosion since it influences the electrochemical reactions and the moisture amount that the concrete retains [135].…”
Section: Evolution Of Data-driven Corrosion Assessmentmentioning
confidence: 99%
“…Under this amount of alkalinity, rebar persists passivated. However, the passivation of rebar is breakdown due to the presence of Cl − or by the carbonation of the concrete [12][13][14]. Carbonation is a natural physicochemical process triggered by the penetration of CO 2 from the neighboring environment into the concrete through pores in the matrix where the CO 2 reacts with hydrated cement [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A convolutional neutral network can support the image analysis of corroded surfaces for its precise definition, in order to improve the accuracy of FEM simulation of structural performances of steel structures [6]. On the other hand, in the case of reinforced concrete structures, it has been demonstrated that the rebar corrosion can depend on its surface state and the passivation and anticorrosion behavior can be improved through rebar surface treatments [7]. Finally, in the case of steel, hot work sliding parts specific surface modifications must be developed for guaranteeing corrosion and wear resistance through boriding or yttria-stabilized zirconia thermal spray coating [8].…”
Section: Effect On Corrosion Behaviormentioning
confidence: 99%
“…However, under aggressive conditions (generally related to carbonation or the presence of chlorides) [1][2][3][4][5][6][7][8], even concrete that has been prepared and applied correctly can lose its protective properties and allow reinforcements to corrode before the minimum of 50 years of its expected useful life have elapsed, sometimes with serious consequences. Therefore, this concept of almost eternal durability is no longer applicable, and indeed the need for continuous maintenance of concrete structures is now recognized, including action and repair on structures with an age of less than 10 years.…”
Section: Introduction 1backgroundmentioning
confidence: 99%